NILAI BUDAYA LEGENDA DATUK MARSAM SANG BELALANG KUNYIT SEBAGAI ALTERNATIF BAHAN AJAR - Intan Kholida Dj. S; Yundi Fitrah; Rahmawati Rahmawati (Universitas Negeri Makassar, 2023)
The Cultural Value of the Legend of Datuk Marsam The Grasshopper Turmeric as an Alternative Teaching Material. This study aims to describe the cultural values in the Legend of Datuk Marsam Sang Grasshopper Turmeric as an alternative teaching material at SMP Adhyaksa 1 Jambi. The method used is a qualitative. The data in this study were obtained from words, sentences, dialogue quotes, and interview results. Sources of data come from the book Legend of Datuk Marsam The Grasshopper Turmeric and teachers. The results of the study found cultural values: 1) relationship with the Creator (praying habits, feelings of gratitude), 2) relationship with nature (correct use of natural resources), 3) relationship with society (conducting deliberations, obedience to customs, maintaining harmony, wise attitude), 4) relationships with other humans (friendliness and courtesy, respect, mutual cooperation, feelings of affection, obedience to parents, keeping promises), and 5) relationships with oneself (maintaining self-esteem, responsibility, courage, assertiveness). This legend book can be used as teaching material.